User Experience-Based Website Development to Increase Customer Satisfaction and Sales of Maidanii Dimsum Business - Cinta Rizkia Zahra Lubis; Salman Munthe (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to analyze and develop a User Experience (UX)-based website to increase customer satisfaction and sales at the Dimsum Maidanii MSME. The background of this study is based on the low level of customer satisfaction with the existing website, where 70% of respondents said they were dissatisfied and 96.7% suggested further development. The research method used is Research and Development (R&D) with a waterfall model, which includes the stages of needs analysis, design, implementation, testing, and maintenance. The research sample consisted of 30 customers, 1 business owner, and 2 media experts. Data collection was carried out through interviews, observations, questionnaires, and sales documentation. The evaluation instrument used the System Usability Scale (SUS) to measure user experience and customer satisfaction. The test results showed a SUS score of 95.7 which is included in the